Effect of hamstring injuries on athlete’s season best performance at return-to-sport phase of rehabilitation: survey of track runners in high altitude training camps in Kenya - Koskei, Emily C.; Karuguti, Wallace; Matheri, Joseph Mwangi (International Journal Of Community Medicine And Public Health, 2023)
Background: Hamstring injuries amongst runners are some of the most prevalent sports injuries. However, the actual impact of these injuries on athlete’s best performance pre-injury is unknown. The objective of this study was to assess the impact of hamstring injury on athletes’ performance at return to sport phase of rehabilitation amongst track runners in Western Kenya. Methods: Observational longitudinal study utilizing quantitative methods were used. The study setting was in the high-altitude western Kenya regions with accredited training camps. The functional assessment scale for hamstring injuries (FASH) was used to screen injuries and an observational checklist to record the conventional rehabilitation strategies. A moderator effect analysis for the variables was conducted followed by a multi-linear regression analysis to establish the effect of injury on performance. The results were presented in summary tables and graphs. Results: A total of 221 (53% response rate) athletes participated in the study as having a hamstring injury. The study found that athletes took more time after injury compared to their personal best and before injury time records. The average best time for full marathoners was 2:17:19.46 (SD±0:10:54.804), before injury 2:18:05.36 (SD±0:11:06.879) and after injury 2:22:12.02 (SD±0:12:45.174). Conclusions: The study concludes that the prevalence of hamstring injuries among endurance runners in Kenya’s Rift Valley region is still so high. The paper recommends emphasis on extensive strength training before return to sport to address deficits in muscle and eccentric strength on return to sport.